Phytochemical and Antioxidant Activity of Blumea balsamifera and Cordyline fruticosa Based on Ethnopharmacology Knowledge of Muara Tae Tribe, East Kalimantan - Sari, Nur Maulida; Aryani, Farida; Wartomo, Wartomo; Hernandi, Muhammad Fikri; Rositah, Erna; Prayitno, Joko (Biology, Medicine, & Natural Product Chemistry, 2023)
Plant use as traditional medicine is still widely practiced in Indonesia. Muara Tae tribe people, West Kutai regency are one of the regions that still rely on Blumea balsamifera and Cordyline fruticosa plants as traditional medicine. This study aims to determine the potential of Blumea balsamifera and Cordyline fruticosa leaves as medicinal plants with phytochemicals and antioxidants. Phytochemical analysis was tested using Harborne and Kokate methods. Antioxidant activity was evaluated by DPPH radical scavenging assay with slight modification. The results of the phytochemical analysis showed that the extracts of n-hexane, ethyl acetate, and ethanol from the leaves of Blumea balsamifera and Cordyline fruticosa contained alkaloids, tannins, and triterpenoids. Antioxidant activity of Blumea balsamifera leaves extract showed that the n-hexane extract display an ability to inhibit DPPH free radical by 50% at 100 ppm concentration, while ethyl acetate and ethanol extracts display an ability by 77% and 81% at 50 ppm concentration. IC50 value of ethyl acetate and ethanol extracts of Blumea balsamifera leaves sequentially were 23.68 µg/mL and 17.59 µg/mL. Antioxidant activity of Cordyline fruticosa leaves extract showed that the n-hexane and ethyl acetate extract display an ability to inhibit DPPH free radical by 45% and 56% at 100 ppm concentration, while ethanol extracts display an ability by 76% at 50 ppm concentration. IC50 value of ethyl acetate and ethanol extracts of Cordyline fruticosa leaves sequentially were 73.72 µg/mL and 20.17 µg/mL. Based on the results, Blumea balsamifera and Cordyline fruticosa leaves extracts had the potential to develop as natural antioxidants.